Psychometric Properties of the Stress and Anxiety to Viral Epidemics-6 Items (SAVE-6) Scale for High School Students During the COVID-19 Pandemic - Lee, Taeyeop; Ahmed, Oli; Akça, Ömer Faruk; Chung, Seockhoon (Frontiers in Psychiatry, 2022)
Objectives: Owing to the COVID-19 pandemic, high school students have experienced a sudden change of school environment, which may result in difficulties related to mental health. The aim of this study is to estimate the reliability and validity of the Stress and Anxiety to Viral Epidemics-6 Items (SAVE-6) scale among high school students. Methods: A cross-sectional online survey was conducted among 300 high school students. The following scales were administered: the SAVE-6, Generalized Anxiety Disorder-7 Items (GAD-7), and Patient Health Questionnaire-9 Items (PHQ-9). Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted, and the psychometric properties of the SAVE-6 were assessed. Results: The results of the CFA indicated good model fit for the SAVE-6 scale among high school students (χ2/df = 0.485, CFI = 1.000, TLI = 1.010, RMSEA < 0.001, and SRMR = 0.029). In addition, the SAVE-6 scale demonstrated good reliability (Cronbach’s alpha = 0.844, McDonald’s Omega = 0.848, and split-half reliability = 0.883). The appropriate cut-off score for the SAVE-6 scale was estimated as ≥15, which corresponds to a mild level of anxiety as assessed by the GAD-7 (≥5). Conclusions: The SAVE-6 scale was found to be reliable and valid, and can be used as a tool to assess the stress and anxiety of high school students during the COVID-19 pandemic.